Workshop Optimalisasi Bahan Ajar Berbasis Aplikasi Canva di SD Negeri 4 Muara Pinang - Dodik Mulyono; As Elly; Nini Andriani; Yeni Yulizah (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
The purpose of this activity is to optimize teaching materials by utilizing the Canva application in designing learning materials in elementary schools. Participants in this workshop were all teachers and operators at 4 Muara Pinang Elementary School, based on current educational challenges such as the independent curriculum and technological advances that affect learning strategies. The methods used were lecture, demonstration, practice and mentoring methods, and evaluation. Data analysis was carried out based on the results of filling out the questionnaire by all participants. The results of the questionnaire analysis given based on several indicators, the indicator of success in making teaching materials showed a percentage of 92.88% with the category "very good." Meanwhile, the indicator of the usefulness of the activity reached a percentage of 94.75%, which was in the category "very useful." This confirms that this workshop has succeeded in improving participants' skills in optimizing teaching materials using technology to support learning. By optimizing the Canva application, it is hoped that teachers can implement an inclusive, equitable, and lifelong learning approach.